24(R, S)-Saringosterol - From artefact to a biological medical agent. Issue 212 (September 2021) - Vanbrabant, Kenneth; Van Meel, David; Kerksiek, Anja; Friedrichs, Silvia; Dubbeldam, Marco; Schepers, Melissa; Zhan, Na; Gutbrod, Katharina; Dörmann, Peter; Liu, Hong-Bing; Mulder, Monique T.; Vanmierlo, Tim; et al.
Graphical abstract: Photooxidative process to convert fucosterol into stereoisomeric 24( R, S )-saringosterol. Highlights: Brown algae extracts are an optimal source for 24( R, S )-saringosterol production. Algae contain photosensitizer agents which mediate 24( R, S )-saringosterol formation. Light-exposed brown algae, efficient biosynthetic 24( R, S )-saringosterol producers. Prolonged temperature profile differentiates stereoisomeric forms of saringosterol. Algae contain comparable amounts of 24( R )- and 24( S )-saringosterol (1:1). Abstract: Enhancing the cholesterol turnover in the brain via activation of liver x receptors can restore memory in a mouse model for Alzheimer's disease. The edible Asian brown alga Sargassum fusiforme (Hijiki) contains high amounts of oxysterols such as (3β, 24ξ)-stigmasta-5, 28-dien-3, 24-diol (24[ R, S ]-saringosterol) that are a potent liver x receptor agonists. We aimed to find native European seaweed species with contents of 24( R, S )-saringosterol that are comparable to those found in Sargassum fusiforme . Additionally, we hypothesize that seasonal variations modify the amount of 24( R, S )-saringosterol in seaweeds. Sterols and oxysterols were extracted with chloroform/methanol from various seaweed species harvested in the Eastern Scheldt in different seasons between October 2016 and September 2017. Identification and quantification of the lipids was performed by gas chromatography- mass spectrometry and gas chromatography- flame ionization detection. We confirmed that brown algae Undaria pinnatifida harvested in February and Sargassum muticum harvested in October contained the highest amounts of 24( R, S )-saringosterol (32.4 ± 15.25 μg/g, mean ± S.D. and 32.95 ± 2.91 μg/g, respectively) and its precursor fucosterol (1.48 ± 0.11 mg/g), higher than Sargassum fusiforme (20.94 ± 3.00 μg/g, mean ± S.D.), while Ascophyllum nodosum and Fucus vesiculosus and Fucus serratus contained amounts of 24( R, S )-saringosterol (22.09 ± 3.45 μg/g, 18.04 ± 0.52 μg/g and 19.47 ± 9.01 μg/g, mean ± S.D., respectively) comparable to Sargassum fusiforme . In other algae only minor amounts of these sterols were observed. The green algae Ulva lactuca contained only 0.29 mg/g fucosterol and 10.3 μg/g 24 ( R, S )-saringosterol, while all investigated red algae did not contain any 24( R, S )-saringosterol or fucosterol. In the Eastern Scheldt algae harvested in September/October delivered the highest yield for 24( R, S )-saringosterol, with the exception of Undaria pinnatifida that showed the highest levels in February. We showed that exposure of lipid extracts of Ulva lactuca to sunlight at room temperature or in the presence of oxygen to UV-C light lead to the quantitative conversion of fucosterol into 24( R, S )-saringosterol. Exposing pure fucosterol to UV-light did not convert any fucosterol into 24( R, S )-saringosterol underscoring the requirement of seaweed constituents in the conversion of fucosterol into 24( R, S )-saringosterol. In conclusion, we showed that brown seaweeds harvested from the Eastern Scheldt contain amounts of 24( R, S )-saringosterol comparable to Sargassum fusiforme, varying per season and showing the highest amounts in spring. In accordance with these observations the amount of 24( R, S )-saringosterol in the brown seaweeds can be modulated by light.